Dynamics of the 137Cs excretion from Prussian carp (Carassius gibelio) at different water temperatures - O. V. Kashparova (Âderna Fìzika ta Energetika, 2019)
Freshwater fish such as Prussian carp (Carassius gibelio) don’t need a feed at a water temperature below 10 °С. To study the rate constants of 137Cs excretion from the body of Prussian carp at different water temperatures (5 and 22 °С) and different feeding, the series of aquarium experiments were conducted. The half-life time of 137Cs activity excretion from fish in the water (T = 5 °С) without feeding (T1/2= 433 ± 162 days) was 5.6 times higher compared to the rate constants for water temperature 22 °С (T1/2 = 78 ± 4 days) with different types of feeding. The temporal decline of 137Cs activity (Bq) in fish was the same for different feeds, but the activity concentration of 137Cs (Bq·kg-1) in fish differed up to 1.8 times (0.0089 ± 0.0005 day-1 and 0.016 ± 0.002 day-1) due to different weight gains.